Hasil Skrining Aktivitas Sitotoksik Ekstrak Etanol Daun Kelengkeng (Dimocarpus longan), Daun Kersen (Muntingia calabura), dan Daun Alpukat (Persea americana) terhadap Sel T47D Dan WiDr - Ratna Yuliani; Broto Santoso; Bella Permatasani; Diah Mukti Sari (Pharmacon: Jurnal Farmasi Indonesia, 2019)
Cancer treatments usually cause adverse drug reactions. Therefore, safe anticancer drugs are needed in the treatment of cancer. One source of medicine that can be explored is plant. Extracts of longan leaves (Dimocarpus longan), jamaican cherry leaves (Muntingia calabura), and avocado leaves (Persea americana) have been tested for cytotoxic activity against several cancer cell lines. This study aims to determine the cytotoxic activity of ethanolic extract of longan leaves, jamaican cherry leaves, and avocado leaves against T47D and WiDr cells and to identify secondary metabolites in the extracts which have the highest activity. Ethanolic extract of longan leaves, jamaican cherry leaves, and avocado leaves were tested for their cytotoxic activity using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) method. Identification of secondary metabolites in the ethanolic extract of avocado leaves was carried out by thin layer chromatography method using silica gel GF254 as the stationary phase and a mixture of n-hexane and acetone (6:4) as the mobile phase. Cytotoxic test results show that ethanolic extract of longan leaves and cherry leaves with concentration of up to 1600 μg/mL do not reduce the T47D and WiDr living cells to 50%. Avocado leaf extract decreases the percentage of living T47D cells and WiDr with IC50 values of  790.679 µg/mL and 1072.2 µg/mL, respectively. The ethanolic extract of avocado leaves contains flavonoid, phenolic, and terpenoid. Ethanolic extract of longan leaves, cherry leaves and avocado leaves do not have cytotoxic activity against T47D and WiDr cells.